(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Liinc em Revista Vol. 7, n. 2 (2011) Link de acesso ao número http://revista.ibict.br/liinc/index.php/liinc/issue/view/38